(untitled) (Ustozlar uchun, 2026)
This article explores the role of English as a global language in international communication. Based on research in Sociolinguistics, the study highlights how English functions as a common medium among people from different linguistic backgrounds. It examines the importance of English in fields such as business, education, science, and technology. The findings indicate that English plays a crucial role in facilitating global interaction, cultural exchange, and access to information. Therefore, mastering English is considered essential in the modern interconnected world.